2016
DOI: 10.1016/j.trc.2016.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Drivers’ rear end collision avoidance behaviors under different levels of situational urgency

Abstract: Rear-end collisions have been estimated to account for 20 to 30 percent of all crashes, and about 10 percent of all fatal crashes. A thorough investigation of drivers' collision avoidance behaviors when exposed to rear end collision risks is needed to help guide the development of effective countermeasures. Urgency or criticality of the situation affects drivers' collision behavior, but has not been systematically investigated. A high fidelity driving simulator was used to examine the effects of differing leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
56
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(64 citation statements)
references
References 25 publications
7
56
1
Order By: Relevance
“…More importantly, the driving simulator tests can be conducted in controlled and high-risk conditions, e.g., potential rear-end collision, while the safety of participants can be ensured which was impossible in real traffic situation presently. Previous studies have shown that driving simulator is a reliable and valid apparatus to examine drivers' behaviour [36][37][38]. Muhrer and Vollrath [39] examined drivers' carfollowing behaviour by varying the lead vehicle's driving status (different braking behaviour, signaling or not before a turn) in a driving simulator experiment.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, the driving simulator tests can be conducted in controlled and high-risk conditions, e.g., potential rear-end collision, while the safety of participants can be ensured which was impossible in real traffic situation presently. Previous studies have shown that driving simulator is a reliable and valid apparatus to examine drivers' behaviour [36][37][38]. Muhrer and Vollrath [39] examined drivers' carfollowing behaviour by varying the lead vehicle's driving status (different braking behaviour, signaling or not before a turn) in a driving simulator experiment.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of the influence of situational urgency on driving responses in either with a warning or without a warning was reported in previous studies (3,12) . Situational urgency can be described by using two types of parameters.…”
Section: Introductionmentioning
confidence: 99%
“…In other study with no warning condition, shorter initial headway and leading vehicle's hard brake tend to cause faster brake reaction time and harder brake profile. Conversely, longer initial headway and leading vehicle's gradual brake usually causes slower brake reaction time and gradual brake profile or multiple-staged brake profile (12) .…”
Section: Introductionmentioning
confidence: 99%
“…Among them, 56% of the accidents occurred in the grade and highway, resulting in 40,676 people were killed and 120,556 injured (Weng et al 2015).With the rapid economic development, China's highway in the past decade has developed very fast, and the total mileage of the highway has reached 125,000 km.Therefore, this led to highway traffic accidents have soared (Wang et al, 2016;Wang et al, 2013).Research shows that China 's highway rear-end accidents accounted for about 40% of all traffic accidents, casualties is accounted for 60% (Wu and Thor, 2015;Xiao, 2016).Rear-end accident is very serious in China's highway. Figure 1 is a highway accident statistics, it can be seen that the proportion of rear-end accidents accounted for the largest, which reaching 34.3% (Wang et al, 2016).Therefore, it is necessary to carry out analysis and research on the rear-end accident, and to grasp its characteristics, especially the analysis of vehicle speed. Highway traffic accident is characterized by rapid speed, vehicle damage and serious casualties, especially the car rear-end collision truck(Abdel-Aty and Abdelwahab, 2003;Alpar and Stojic,2016).There are many research on early warning of the rear-end accident onhighway.…”
Section: Introductionmentioning
confidence: 99%
“…Highway traffic accident is characterized by rapid speed, vehicle damage and serious casualties, especially the car rear-end collision truck(Abdel-Aty and Abdelwahab, 2003;Alpar and Stojic,2016).There are many research on early warning of the rear-end accident onhighway. The early-warning system usually considers the braking performance, vehicle speed and the vehicle type characteristics (Alpar and Stojic,2016;Wang et al,2016;Rakha et al, 2010;Yoshida et al, 2016).When a rear-end accident occurs on a highway, the latter usually leaves the brake imprints and scatters at the scene, which can generally be used to calculate the speed of the vehicle (Kim et al, 2007;Yi et al, 2011).In the accident, the vehicle speed in front of the rear-end collision can be difficult to obtain due to the passive nature and the instantaneous nature of the accident, and it is generally too late to take measures at the moment of the collision (Fildes et al, 2015;Germán, 2013;Yan et al, 2009). …”
Section: Introductionmentioning
confidence: 99%